Gas turbine working grid profiles design via inverse problem - Субботович, Валерий Петрович (Eastern-European Journal of Enterprise Technologies, 2013)
Application of existing methods of solution of direct and inverse problems for the 3D-flow at optimal design of turbomachinery grids is associated with big problems, and the method of solution of the inverse problem even for the Q3D-flow, which takes into account the characteristics of the organization of the process of optimization search, opens up new possibilities for the design. The causes for the development of a new method were also positive results of experimental studies of the grid of the nozzle profiles with wavy shapes of trough and back, designed via the inverse problem for the 2D-current, which were conducted by the author. The direct and inverse problems for the Q3D-flow were divided into separate subtasks that could have been solved in any order or simultaneously. This provided the possibility to control any part of the designed blade in terms of strength and technological effectiveness, which could significantly reduce design time. The individual subtasks were solved by the methods of nonlinear programming that did not require storage of significant amounts of information. The parameters of the flow in the interblade channels for the fixed and rotating working grid of a gas turbine were determined, using the direct problem. Applying the inverse problem the interblade channels of grids were designed and the effect of rotation of the form of the surface of current and the aerodynamic boundary conditions on the coefficient of the profile losses of the grid and the geometric characteristics of profiles was shown.